The Role of Social Media Analytics in Optimizing Consumer Engagement and Digital Advertising Campaigns - Heriyana Heriyana; Hendri Setiadi; Rekno Sulandjari; Andita Andita; Faizah Syihab (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The rapid growth of digital technology has transformed social media into a strategic platform for consumer interaction and digital advertising. Organizations are increasingly required to utilize data-driven approaches to improve marketing effectiveness. This study aims to analyze the role of social media analytics in enhancing consumer engagement and optimizing digital advertising campaign performance in the Indonesian context. A qualitative research design using a systematic literature review was employed. Data were collected from reputable academic databases, including Scopus, Web of Science, Google Scholar, and ScienceDirect. The selected studies were analyzed using content analysis and thematic synthesis to identify key patterns and relationships among variables. The findings indicate that social media analytics significantly improves consumer engagement through content optimization, sentiment analysis, personalization, and influencer evaluation. In addition, analytics enhances advertising effectiveness by enabling precise targeting, real-time performance monitoring, and cross-channel attribution. These mechanisms contribute to higher click-through rates, conversion rates, and return on advertising spend. The study confirms that social media analytics supports evidence-based marketing decisions and strengthens competitive advantage in the digital marketplace. The results provide both theoretical and practical implications for organizations seeking to improve their digital marketing strategies through data-driven approaches.